Review of 502 patients with upper gastrointestinal bleeding - Fulya GÜNŞAR; Ulus Salih AKARCA; Nadir YÖNETÇİ and Ömer ÖZÜTEMİZ and Ahmet AYDIN and Galip ERSÖZ and Serhat BOR and Ahmet MUSAOĞLU and Hanefi ÇAVUŞOĞLU and Yücel BATUR (Turkish Journal of Gastroenterology, 2019)
-